2020
DOI: 10.1016/j.celrep.2020.107680
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-Mediated Protein Disaggregation Triggers Proteolytic Clearance of Intra-nuclear Protein Inclusions

Abstract: Highlights d Nuclear Hsp40 Apj1 mediates proteolytic clearance of intranuclear protein inclusions d Apj1 supports Hsp104-independent disaggregation in vitro and in vivo d Apj1 competes with Hsp104 in disaggregation, supporting turnover instead of refolding d Inside the nucleus, Apj1 functions in quality control of nuclear and cytoplasmic proteins Authors Fabian den Brave,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 67 publications
2
49
0
Order By: Relevance
“…The involvement of the Hsp40 co-chaperone in the proteasome-dependent disaggregation of transient-QC is in line with findings that established Hsp40 co-chaperones not only as Hsp70 activators but also as regulators of their binding specificity and functional diversity [32][33][34][35]. Now, the den Brave study, not only establishes the function of the nuclear Hsp40, Apj1, in INQ clearance, but it also indicates that Hsp104-dependent refolding and proteasome-mediated degradation of solubilized misfolded proteins are independent disaggregation triage reactions [32]. Yet, Hsp104 activity is required for the turnover of aggregation-prone, membrane-embedded, Endoplasmic Reticulum-Associated Degradation (ERAD) substrates, but not for their soluble counterparts [36].…”
Section: Misfolded Proteins Are Extracted From Cell Inclusions and Sosupporting
confidence: 87%
See 4 more Smart Citations
“…The involvement of the Hsp40 co-chaperone in the proteasome-dependent disaggregation of transient-QC is in line with findings that established Hsp40 co-chaperones not only as Hsp70 activators but also as regulators of their binding specificity and functional diversity [32][33][34][35]. Now, the den Brave study, not only establishes the function of the nuclear Hsp40, Apj1, in INQ clearance, but it also indicates that Hsp104-dependent refolding and proteasome-mediated degradation of solubilized misfolded proteins are independent disaggregation triage reactions [32]. Yet, Hsp104 activity is required for the turnover of aggregation-prone, membrane-embedded, Endoplasmic Reticulum-Associated Degradation (ERAD) substrates, but not for their soluble counterparts [36].…”
Section: Misfolded Proteins Are Extracted From Cell Inclusions and Sosupporting
confidence: 87%
“…A recent study from the late Stephan Jentsch lab [31] has demonstrated that the yeast Hsp70/Apj1 bi-chaperone pair, in cooperation with Hsp110, exclusively couples the dissolution of INQ to 26S proteasome-mediated degradation, independently of Hsp104 function [32]. The involvement of the Hsp40 co-chaperone in the proteasome-dependent disaggregation of transient-QC is in line with findings that established Hsp40 co-chaperones not only as Hsp70 activators but also as regulators of their binding specificity and functional diversity [32][33][34][35]. Now, the den Brave study, not only establishes the function of the nuclear Hsp40, Apj1, in INQ clearance, but it also indicates that Hsp104-dependent refolding and proteasome-mediated degradation of solubilized misfolded proteins are independent disaggregation triage reactions [32].…”
Section: Misfolded Proteins Are Extracted From Cell Inclusions and Somentioning
confidence: 99%
See 3 more Smart Citations